Genetic variations in somatostatin gene and their association with body weight and morphometric traits in two sheep breeds - R.S. Aljubouri, Thamer; M. Al-Khafaji, Firas; Alwan, Haider (Agriculture and Natural Resources, 2026)
Importance of Work: Somatostatin (SST) is a peptide hormone that regulates growth, metabolism and reproduction in sheep. Given the pronounced growth differences between the Awassi and Karakul breeds, investigating SST-related genetic variation may help explain these disparities. Objectives: To identify polymorphisms in the SST gene and to evaluate their potential association with growth performance in Awassi and Karakul sheep. Materials and Methods: In total, 175 sheep were evaluated, comprising 100 Awassi and 75 Karakul. Various growth trait indices were monitored in five successive time intervals, from birth to age 12 mth. Genotyping was performed using polymerase chain reaction–single strand conformation polymorphism analysis, followed by electrophoretic identification of genotypes. The detected single nucleotide polymorphisms (SNPs) were confirmed based on Sanger sequencing. Genotype-phenotype associations were analyzed using a linear mixed model to account for repeated measures and the fixed effects of genotype, breed, sex and season. Results: No polymorphism was detected in exon 2, whereas a novel silent SNP (154G>A; p.Q36=) was identified in exon 1. While no significant genotype differences were observed at birth for any measured traits, the 154G>A SNP showed significant associations (p < 0.01) with body weight, body length, and rump and wither heights from age 3 mth onward. Animals with the AA genotype had higher values for these traits than those with the GA and GG genotypes. In addition, the GA and AA genotypes occurred at higher frequencies in Karakul lambs than in Awassi lambs. The 154G>A SNP may serve as a potential marker for growth selection; however, the present findings, based on a moderate sample size and polygenic traits, require validation in larger and independent sheep populations. Main Findings: The identified 154G>A SNP in the SST gene was associated strongly with postnatal growth performance in sheep and may serve as a useful molecular marker for selection programs. Its higher prevalence in Karakul sheep could partly explain the superior growth performance observed in this breed compared to Awassi sheep.